Dealer risk limits and currency returns - Omar Barbiero; Falk Bräuning; Gustavo Joaquim; Hillary Stein (Federal Reserve Bank of Boston, 2024)
We leverage supervisory microdata to uncover the role of global banks' risk limits in driving exchange rate dynamics. Consistent with a model of currency intermediation under risk constraints, shocks to dealers' risk limits lead to price and quantity adjustments in the foreign exchange market. We show that dealers adjust their net position and increase the bid-ask spread in response to granularly identified limit shocks, leading to lower turnover and an adjustment in currency returns. These shocks exacerbate the effects of net currency demand on exchange rate movements, as predicted by theory, and trigger deviations from covered interest parity.
Keywords: F31; G15; G21; 330; Exchange rates; currency returns; market making; risk constraints; financial intermediation